Gene transfer from targeted liposomes to specific lymphoid cells by electroporation. - Machy, P (1988)
Large unilamellar liposomes, coated with protein A and encapsulating the gene that confers resistance to mycophenolic acid, were used as a model system to demonstrate gene transfer into specific lymphoid cells. Protein A, which selectively recognizes mouse IgG2a antibodies, was coupled to liposomes to target them specifically to defined cell types coated with IgG2a antibody. Protein A-coated liposomes bound human B lymphoblastoid cells preincubated with a mouse IgG2a anti-HLA monoclonal antibody but failed to adhere to cells challenged with an irrelevant (anti-H-2) antibody of the same isotype or to cells incubated in the absence of antibody. Transfection of target cells bound to protein A-coated liposomes was achieved by electroporation. This step was essential since only electroporated cells survived in a selective medium containing mycophenolic acid. Transfection efficiency with electroporation and targeted liposomes was as efficient as conventional procedures that used unencapsulated plasmids free in solution but, in the latter case, cell selectivity is not possible. This technique provides a methodology for introducing defined biological macromolecules into specific cell types.